INVARIANT SUBMANIFOLD OF (3k,k)STRUCTURE MANIFOLD - Singh, Lakhan; Gautam, Shailendra Kumar (IJRDO -JOURNAL OF MATHEMATICS, 2016)
In this paper, we have studied various properties of a3 , k k structuremanifold and its invariant submanifold, where k is positive integer. Under twodifferent assumptions, the nature of induced structure, has also been discussed.